2005
DOI: 10.1111/j.1469-7610.2004.00363.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity, binge eating, and night eating in a cross‐sectional field survey of 6‐year‐old children and their parents in a German urban population

Abstract: In concurrence with studies on adulthood, binge eating is linked to obesity already in early childhood. Children of mothers with eating disorders and children of mothers with a non-German native language are at increased risk of developing eating disorders themselves. Future studies should focus on obesity and eating disorders in early childhood; prevention programs should seek to target young children at risk as early as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 41 publications
9
69
0
4
Order By: Relevance
“…Two prevalence studies of NES in the general population for adults revealed rates of 1.5% (Rand et al, 1997) and 5.2% (Lamerz et al, 2005). Prevalence estimates in obesity clinics are higher, ranging from 6% (Cerú-Björk et al, 2001) to 14% (Gluck, Geliebter, & Satov, 2001), and in pre-operative bariatric surgery patients from 8% (Adami, Meneghelli, & Scopinaro, 1999;Allison et al, 2006) to 42% (Hsu, Bentancourt, & Sullivan, 1996).…”
Section: Nih Public Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Two prevalence studies of NES in the general population for adults revealed rates of 1.5% (Rand et al, 1997) and 5.2% (Lamerz et al, 2005). Prevalence estimates in obesity clinics are higher, ranging from 6% (Cerú-Björk et al, 2001) to 14% (Gluck, Geliebter, & Satov, 2001), and in pre-operative bariatric surgery patients from 8% (Adami, Meneghelli, & Scopinaro, 1999;Allison et al, 2006) to 42% (Hsu, Bentancourt, & Sullivan, 1996).…”
Section: Nih Public Accessmentioning
confidence: 99%
“…Some NES studies have examined putative NES samples which have had nocturnal ingestions or evening hyperphagia (Cerú-Björk et al, 2001, Grilo & Masheb, 2004Napolitano, Head, Babyak, & Blumenthal, 2001) as well as samples that included persons who had either of these or both criteria (Allison et al, 2007;Allison et al, 2006;Allison et al, 2005;O'Reardon et al, 2004;Pawlow, O'Neil, & Malcolm, 2003). Striegel-Moore and colleagues (2004, 2006) tested several of these definitions with a sample of adolescent girls and a representative national sample ages 13 and older, demonstrating decreases in the proportion of those reporting nocturnal eating with increasingly stringent criteria.Two prevalence studies of NES in the general population for adults revealed rates of 1.5% (Rand et al, 1997) and 5.2% (Lamerz et al, 2005). Prevalence estimates in obesity clinics are higher, ranging from 6% (Cerú-Björk et al, 2001) to 14% (Gluck, Geliebter, & Satov, 2001), and in pre-operative bariatric surgery patients from 8% (Adami, Meneghelli, & Scopinaro, 1999;Allison et al, 2006) to 42% (Hsu, Bentancourt, & Sullivan, 1996).…”
mentioning
confidence: 99%
“…51,52 The Children's Depression Inventory (CDI) is a 26-item self report questionnaire of depressive feelings for ages [8][9][10][11][12][13][14][15][16]. Internal consistency of the total score of the German version is high, convergent, and discriminant validity have been demonstrated.…”
Section: Methodsmentioning
confidence: 99%
“…7 Only a small subset of children and adolescents meet full Diagnostic and Statistical Manual of Mental Disorders (DSM)-IV-TR criteria for BED, while the experience of LOC eating and emotional eating seem to be more common. 6,[8][9][10][11][12][13][14] Research indicates that emotional eating and binge eating in children and adolescents are associated with anxiety, sadness, and anger 6,12,15 which has previously been shown in adults. [16][17][18][19][20][21] Overweight children 8,12,14 and adolescents 9,10,22 with LOC eating were shown to experience greater eating-related distress, anxiety, and depressive symptoms than those without LOC eating.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of non-treatment seeking children aged 6 to 14 years using questionnaire and survey reports to assess binge eating have found prevalence ranges from approximately 2% to 10% (Field et al, 1999;Lamerz et al, 2005;Maloney, McGuire, Daniels, & Specker, 1989). None of these investigations assessed for the full DSM-IV-TR criteria for binge eating disorder (APA, 2000).…”
Section: Prevalence Of Loc Eating and Associations With Overweightmentioning
confidence: 99%